2007
DOI: 10.1111/j.1529-8817.2007.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION AND COMPARATIVE GENOMIC ANALYSIS OF SIGNALING AND REGULATORY COMPONENTS IN THE DIATOM THALASSIOSIRA PSEUDONANA1

Abstract: Diatoms are unicellular brown algae that likely arose from the endocytobiosis of a red alga into a single‐celled heterotroph and that constitute an algal class of major importance in phytoplankton communities around the globe. The first whole‐genome sequence from a diatom species, Thalassiosira  pseudonana Hasle et Heimdal, was recently reported, and features that are central to diatom physiology and ecology, such as silicon and nitrogen metabolism, iron uptake, and carbon concentration mechanisms, were descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 117 publications
3
63
4
Order By: Relevance
“…The phenomenon of photoperiodism is not well-studied in marine phytoplankton, but the presence of phytochromes in nearly all cyanobacteria and eukaryotic algae studied to date, including marine diatoms (68), suggests that these light-activated molecular switches may be common in the sea. Thus, we propose that activation of phytochromes by astronomical influences, especially variations in photoperiod following the "turning of the sun," may initiate a genetically controlled cascade of molecular and metabolic processes that ultimately define the end of summer and trigger the SEP that we describe herein.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of photoperiodism is not well-studied in marine phytoplankton, but the presence of phytochromes in nearly all cyanobacteria and eukaryotic algae studied to date, including marine diatoms (68), suggests that these light-activated molecular switches may be common in the sea. Thus, we propose that activation of phytochromes by astronomical influences, especially variations in photoperiod following the "turning of the sun," may initiate a genetically controlled cascade of molecular and metabolic processes that ultimately define the end of summer and trigger the SEP that we describe herein.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of diatoms to adjust their physiology in response to the diurnal cycle and growth phase fundamentally depends on sensing, signaling, and regulatory mechanisms (38,39). The expression levels of 41% of known transcription factors, 35% of all potential signaling domains, and 31% of genes involved in chromatin state dynamics were up-regulated under one or more of the four identified growth states (Fig.…”
Section: Transition From Exponential Growth To Nutrient-depleted Statmentioning
confidence: 99%
“…These include photomorphogenesis and the entrainment of the circadian clock in higher plants (40). Diatoms contain multiple photoreceptors to sense and respond to light signals of varying and specific spectral properties (38,39). In T. pseudonana, one (far) red-light photoreceptor (diatom phytochrome DPh), four blue-light cryptochrome/photolyase family proteins (CPF1-4), and four aureochrome-like blue-light-regulated transcription factors have been identified (38,39,41,42).…”
Section: Transition From Exponential Growth To Nutrient-depleted Statmentioning
confidence: 99%
“…Opposing the classical view of phytoplankton cells as only passive drifters, recent research conducted on diverse phytoplankton have shown their ability to sense and respond to changing environmental conditions by employing specific acclimation mechanisms (Falciatore et al, 2000;Vardi et al, 2002Vardi et al, , 2006Montsant et al, 2007;Taylor, 2009;McLachlan et al, 2012;Graff van Creveld et al, 2014).…”
Section: Introductionmentioning
confidence: 99%